Memorandum of understanding between Universiti Teknologi MARA and Universitas Padjadjaran / Fakulti Perakaunan - Universiti Teknologi MARA, Fakulti Perakaunan (Universiti Teknologi MARA (UiTM), 2018)
In order to promote further the existing scientific research and projects cooperation between UiTM and Universitas Padjadjaran.